Musicians’ career development: educational and financial support in Finland - Metsalo, Maria (Taideyliopiston Sibelius-Akatemia, 2023)
This thesis outlines existing opportunities and possibilities for musicians and music industry professionals in getting support both in educational and financial form in Finland for their career development. Focus of the thesis is to map available masterclasses, courses, mentorships opportunities that give support and help in further career development, entrepreneurial skills, internationalization, and music export. Also, funding possibilities for musicians are mapped. This study researches and reflects on the needs and requirements of musicians and the importance of support for creative businesses and entrepreneurship. As the music industry has gone through rapid changes in the past decades related to digitalization and music distribution, more load is put on artists for them to independently take care of various aspects of their career development. There is greater need to educate creatives about entrepreneurship and self-management skills. Digital transformations have remodelled the way record labels and artist management companies work, and additional skills and knowledge is required to cope in the market both for musicians and music companies. This study examines what kind of support there is available in Finland and what kind of institutions or entities offer opportunities to learn and develop these needed skills. Purpose of this research is to find out what kind of mentorship and development possibilities for musicians and music companies are available and to research on the accessibility of such programs. This research is carried out as a literature review and qualitative case study where participants of Music Finland’s International Music Business Masterclass 2022-2023 are surveyed about the above- mentioned research topics. In addition, semi-structured interviews are carried out with representatives of three music industry related organizations.
Keywords: musiikki; yrittäjyys; musiikkiala; urakehitys; muusikot; urasuunnittelu; fi=taidehallinto|sv=Arts Management|en=Arts Management|